The human factor the demography of the Roman province of Hispania Citerior/Tarraconensis - Sinner, Alejandro G. ca. 20./21. Jh; Carreras Monfort, Cèsar; Houten, Pieter Hubert Antoine 1984- (Oxford University Press, 2024)
'The Human Factor' establishes a foundation for the study of ancient demography in the Iberian Peninsula, focusing on its largest province, Hispania Citerior/Tarraconensis. The authors take a multidisciplinary approach, compiling archaeological, epigraphic, architectonic, osteological, and genetic datasets. This comprehensive and detailed study of a single province is necessary to generate accurate demographic estimates and to compare it with datasets from other regions and historical periods. By examining the province of Hispania Citerior/Tarraconensis in depth, the authors provide a detailed understanding of demographic patterns, urbanism, and urbanization rates over time, and link them with the social, cultural, and economic factors that affected the Iberian Peninsula and the Western Mediterranean from the fourth century BC until the end of the Roman period
Keywords: Geschichte 400 v. Chr.-400; Society / ukslc; Sociology & anthropology / thema; Bevölkerungsentwicklung; Bevölkerungsstruktur; Spain / Population / History / To 1500; Spain / History / Roman period, 218 B.C.-414 A.D.; Hispania citerior; Hispania Tarraconensis; Bibliografie